A double-edged sword: Children's experiences of visiting a parent in prison in Scotland. (June 2022) - Lockwood, Kelly; Long, Tony; Loucks, Nancy; Raikes, Ben; Sharratt, Kathryn
Prison visits are recognised as an important feature of a humane prison system, providing important benefits for prisoners and their family in maintaining ties (McCarthy and Adams, 2017). Scotland has a history of penal welfarism and a right-based agenda in relation to visits (McCarthy and Adams, 2017); however, there is a lack of research that focuses on visits in the context of Scottish prisons. Equally, there is limited research that considers the perspective of children visiting a parent in custody. This paper explores the experiences of children visiting a parent in prison in Scotland, highlighting lessons for policy and practice.